Dynamic simulation of a 3-D 4BL engineering problem using augmented reality - Sidhu M.S.; Maqableh W. (2023)
Multimedia and augmented reality (AR) are fast growing technologies for interactivity and visualization purposes. One domain where these technologies would be useful is in showing interactive animation engineering concepts which are otherwise difficult to be visualized from static images. This paper addresses a new technique to design and simulate an engineering problem i.e. four bar linkage (4BL) mechanism. We adopted multimedia and AR technologies to model the selected engineering problem to help students in the understanding and visualization process. The problem was modeled using an AR toolkit to simulate the four bar linkages that allow users to input the values based on Grashofs law and show the correct orientations with motion of the 4BL mechanism in a real time 3D environment. The design approach showed that the simulation tool helped students in understanding the motion of the 4BL mechanism problem better.